Insecticide resistance in the field populations of the Asian tiger mosquito Aedes albopictus in Beijing: resistance status and associated detoxification genes - Zhou, Xiaojie; Li, Jing; Ni, Ruoyao; Qiu, Xinghui; Zhang, Yong; Tong, Ying (Frontiers in Physiology, 2024)
BackgroundAedes (Stegomyia) albopictus (Skuse) is an invasive and widespread mosquito species that can transmit dengue, chikungunya, yellow fever, and Zika viruses. Its control heavily relies on the use of insecticides. However, the efficacy of the insecticide-based intervention is threatened by the increasing development of resistance to available insecticides. Understanding the current status and potential mechanisms of insecticide resistance is an important prerequisite for devising strategies to maintain the sustainability of vector control programs. In this study, we investigated the current status and probable candidate detoxification genes associated with insecticide resistance in the Asian tiger mosquito in Beijing, the capital city of China.MethodsBioassays were conducted on three field populations of Ae. albopictus collected from urban communities in Beijing by exposure to diagnostic doses of permethrin, deltamethrin, malathion, and propoxur. Differentially expressed genes (DEGs) associated with insecticide resistance were screened by transcriptomic analysis using Illumina RNA sequencing data (RNA-seq) from 12 independent RNA libraries constructed from female strains of the three field populations and one susceptible strain.ResultsThe bioassay results indicated that all the three field populations were resistant to propoxur (carbamate), deltamethrin, and permethrin (pyrethroids), but susceptible to malathion (organophosphate). Eighteen (18) cytochrome P450s (P450s), five (5) glutathione S-transferases (GSTs), four (4) carboxy/cholinesterases (CCEs), eight (8) UDP-glycosyltransferases (UGTs), and three (3) ATP-binding cassette transporters (ABCs) were found to be significantly overexpressed in the three field populations relative to the susceptible strain via transcriptomic analysis.ConclusionThis study demonstrates that the Ae. albopictus field populations in Beijing exhibit multiple phenotypic resistance to commonly used pyrethroids and carbamate. The identification of a number of DEGs associated with insecticide resistance indicates that the mechanisms underlying resistance in field populations are complicated, and detoxifying enzymes may play important roles. The multiple resistance status detected in the three field populations suggests that resistance management strategies such as insecticide rotation and non-chemical-based measures should be implemented in order to sustain effective control of the disease vector and vector-borne diseases.